Rights of the Posted Workers – Directive 96/71/EC and the Evolution of Legislation Concerning Posted Workers - Kochanowski, Maciej (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The aim of the study is to analyse the conflict of rights of posted workers with entre-preneurs’ freedom to provide services in posting of workers Directive 96/71/EC and the enforcement Directive 2014/67/EC. The author presents the key issues of the conflict, as well as its evolution in EU legislation and in European Court of Justice judgments.